(untitled) (Zaporizhzhia Historical Review, 2021)
The politics of the Soviet State concerning the private small and cottage industry during the period of the New Economic Policy (the case of Moscow) are the subject of the article. On the representative sources base the author proved that the Soviet government was interested in development of the private small and cottage industry in order to overcome the economical crisis in the country.